النظام القانوني لعقد الاعتماد الايجاري - شيماء, بن فرج الله (جامعة الوادي - University eloued, 2022)
إن عقد الإعتماد الإيجاري عقد حديث النشأه أنشأه العرف والتعامل التجاري لتلبيه الحاجات الاقتصاديه والمالية ولمواكبة التطور الواقع في مجال التجارة والإستثمار وخاصة في وسائل الإنتاج، وهذا من أجل تمويل الإستثمارات الإنتاجية، وتقديم المساعدة للمشروعات الصغيرة والمتوسطة من خلال رفع إنتاجها، ومن مزايا هذا العقد أنه يعتبر من وسائل التمويل الأقل خطورة بالنسبة للممول مقارنة بالوسائل الأخرى. ولقد نظم المشرع الجزائري هذا العقد بعد الإصلاحات الإقتصادية، وخصص له أحكام خاصة بموجب الأمر رقم 96_09 المتعلق بالإعتماد الإيجاري، وميزه عن باقي العقود الأخرى نظرا للخصوصية التي يمتاز بها، وعليه يمكننا من خلال هذه الدراسة إستخلاص بعض النتائج وهي: -لإبرام عقد الإعتماد الاجثاري يجب أن يمر بمراحل تمهيدية لتطابق الإيجاب والقبول، ليتمكن المؤجر من دراسة الطلب من كافة جوانبه، و إذا وافق المؤجر على هذا الطلب يوكل أمر شراء الأصول والتفاوض بشأنها مع المستأجر. -عقد الإعتماد الإيجاري عقد ثنائي الأطراف في تكوينه، ولكن في تنفيذه فهو ثلاثي الأطراف، يشترط تدخل طرف ثالث كالمورد أو المقاول. - يتمثل محل عقد الإعتماد الإيجاري في الأصل الإنتاجي في أصول منقولة تنقسم إلى منقولات مادية و منقولات معنوية،أما الأصول الغير منقولة تنقسم إلى عقارات بالتخصيص وعقارات بطبيعتها، و اشترط المشرع أن تكون مخصصة لأغراض مهنية أي ليست. The rental credit contract is a newly established contract established by custom and commercial dealings to meet the economic and financial needs and to keep pace with the development in the field of trade and investment, especially in the means of production, and this is in order to finance productive investments and provide assistance to small and medium enterprises by raising their production, and one of the advantages of this contract is that it is considered It is one of the least risky financing methods for the financier compared to other means. The Algerian legislator organized this contract after the economic reforms, and assigned special provisions to it under Ordinance No. 96_09 related to rental credit, and distinguished it from the rest of the other contracts due to its specificity. Accordingly, we can, through this study, derive some results, namely: - To conclude a multi-accreditation contract, it must go through preliminary stages to match the offer and acceptance, so that the lessor can study the request in all its aspects, and if the lessor agrees to this request, the order to purchase the assets and negotiate them with the lessee. The rental credit contract is a bilateral contract in its formation, but in its implementation it is tripartite, requiring the intervention of a third party such as the supplier or contractor. The subject of the rental credit contract in the productive asset is movable assets that are divided into tangible movables and moral movables, while immovable assets are divided into real estate by allocation and real estate by nature
مذكرة ماستر
Keywords: النظام القانوني، الاعتماد الايجاري، قانون أعمال; legal system, rental credit, business law